THE BEGINNING OF MODERNISM IN THE MUSIC OF SERBIAN COMPOSERS - TOTAN, Virđinia; COROIU, Petruța Maria (Studia Universitatis Babes-Bolyai Musica, 2022)
Significantly penetrating the years between the two world wars, this situation testifies to the long process of uneven development of Serbian music. Despite the founding of the Belgrade Opera (1920), the gradual growth of performing qualities, the expansion of the repertoire, the premiere of the first Serbian musical and dramatic achievements of modern expression, the influence of popular music remains an almost exclusive privilege of traditional national forms of music. In order to establish internal continuity, they modernized and expanded the existing tradition with new genres, appreciating that sudden new leaps in language can be accepted primarily in those genres that have already gained some continuity in national music. REZUMAT. ÎNCEPUTURILE MODERNISMULUI ÎN MUZICA COMPOZITORILOR SÂRBI. Pătrunzând semnificativ în anii dintre cele două războaie mondiale, această situație atestă lungul proces de dezvoltare inegală a muzicii sârbești. În pofida înființării Operei din Belgrad (1920), a creșterii treptate a calităților interpretative, a extinderii repertoriului, a premierei primelor realizări muzicale și dramatice sârbești de expresie modernă, influența muzicii populare rămâne un privilegiu aproape exclusiv al formelor naționale tradiționale de muzică. Pentru a stabili o continuitate internă, acestea au modernizat și au extins tradiția existentă cu noi genuri, apreciind că salturile noi și bruște în limbaj pot fi acceptate în primul rând în acele genuri care au dobândit deja o anumită continuitate în muzica națională. Cuvinte cheie: modernism, sârbă, tradiție, naționalism, genuri.